LONGITUDINAL QUADRICEPS STRENGTH AND FALL INJURIES IN MEDICARE CLAIMS: THE HEALTH ABC STUDY. (16th November 2018) - Winger, M; Boudreau, R; Newman, A; Cauley, J; Caserotti, P; Harris, T; Waters, T; Strotmeyer, E
Abstract: Lower-extremity quadriceps strength may be related to incident falls and fall injury. Non-fracture fall injuries (NFFI) are common though not typically included in fall injury studies of older adults. The Health, Aging and Body Composition (Health ABC) Study (N=1, 653, aged 73.5 ± 2.8 years, 52% women, 37% black) included quadriceps strength assessments longitudinally and fall injuries from Medicare Fee-For-Service (FFS) Parts A and B claims, including NFFI and fractures. Quadriceps strength (Nm/kg body weight) was measured with a Kin-Com isokinetic dynamometer at baseline (1997–98) and ≥1 follow-up for up to 5 exams (1998–99, N=1, 528; 2000–01; 2002–03; 2004–05; 2006–07, N=906). Fall injuries occurred in 33% (N=538/1, 653), including NFFI (8%; N=131/1, 653) and fractures (25%; N=407/1, 653). Follow-up was 7.5 ± 3.7 years (NFFI: 4.9 ± 3.4 years; fracture: 5.0 ± 3.3 years; no fall injury: 8.7 ± 3.2 years) with censoring at time of event, death or end of follow-up. In Cox proportional hazards regression with time-varying quadriceps strength multivariable-adjusted for demographics, height, cognition and medication use, 1 Nm/kg lower quadriceps strength/kg was associated with 17% higher incident fall injury risk (95%CI=1.03–1.31). Results were consistent for fracture (HR=1.20; 95%CI=1.04–1.38), though quadriceps strength/kg was not significantly related to NFFI (HR=1.16; 95%CI=0.93–1.46). Percent change in quadriceps strength/kg from baseline was not associated with all fall injuries or injury type (NFFI or fracture). The quadriceps strength/kg proximal to the fall may be more important for predicting incident fall injuries than percent change in strength longitudinally. Lower-extremity strength and fall injury should be investigated in additional older populations at risk for fall injury and fractures.